A rare case of nasal gout. Issue 10 (30th October 2020) - Richards, Emma; Watts, Emma; McClelland, Lisha
Abstract : Gout is an increasingly common metabolic disorder worldwide. Classical presentation is with acute attacks of arthritis affecting the first metatarsophalangeal joint. With disease progression, tophi may also appear. We present an unusual case of nasal gout in a 55-year-old man who was referred to the Ear, Nose and Throat department with irregularity over the nasal bones and episodic pain. We discuss the work up, diagnosis and management of this case and review the limited literature on this topic.